2009
DOI: 10.1111/j.1526-4610.2009.01518.x
|View full text |Cite
|
Sign up to set email alerts
|

Zolmitriptan Nasal Spray in the Acute Treatment of Cluster Headache: A Meta‐Analysis of Two Studies

Abstract: Zolmitriptan nasal spray at a dose of 5 mg and 10 mg is efficacious in the acute treatment of episodic and chronic cluster headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 19 publications
2
19
0
3
Order By: Relevance
“…A recent review of medical treatments for cluster headache (Tyagi 2009) identified the same studies involving triptans as this review, but did not carry out any meta-analyses, while a meta-analysis of the two included studies of intranasal zolmitriptan (Hedlund 2009) is in agreement with findings in this review. A recent Cochrane review of oxygen therapy for migraine and cluster headache (Bennett 2008), found weak evidence for efficacy of normobaric oxygen therapy in treating acute cluster headache based on 19 participants in a double blind cross-over study comparing oxygen therapy and air, and 50 participants in an open cross-over study comparing oxygen therapy with ergotamine tartrate.…”
Section: Agreements and Disagreements With Other Studies Or Reviewssupporting
confidence: 53%
“…A recent review of medical treatments for cluster headache (Tyagi 2009) identified the same studies involving triptans as this review, but did not carry out any meta-analyses, while a meta-analysis of the two included studies of intranasal zolmitriptan (Hedlund 2009) is in agreement with findings in this review. A recent Cochrane review of oxygen therapy for migraine and cluster headache (Bennett 2008), found weak evidence for efficacy of normobaric oxygen therapy in treating acute cluster headache based on 19 participants in a double blind cross-over study comparing oxygen therapy and air, and 50 participants in an open cross-over study comparing oxygen therapy with ergotamine tartrate.…”
Section: Agreements and Disagreements With Other Studies Or Reviewssupporting
confidence: 53%
“…There is generally little reporting of effect size and its precision, which was only presented in seven abstracts [17, 26, 34, 3638, 45]. Effect size (active minus control) in percentages or absolute value, with 95% confidence intervals (CI), is the clinically relevant measure.…”
Section: Commentsmentioning
confidence: 99%
“…Since expression data on all individual subjects was available for the outcome of risk of breast cancer, we also conducted individual patient data (IPD) meta-analysis [16]. For this we used the clustered unconditional logistic regression analyses [16,17] with disease status as a dichotomous dependent variable, comparison-specific z-scores as the predictor variable and comparison indicator as the clustering variable. Comparison-specific z-scores were estimated as the relative deviates (mean expression/standard deviation of expression) within each comparison group.…”
Section: Methodsmentioning
confidence: 99%